0044 Pre-Pandemic Circadian Phase Predicts Pandemic Sleep, Depression, and Alcohol Use Among Adolescents. (25th May 2022) - Hasler, Brant; Wallace, Meredith; Graves, Jessica; Buysse, Daniel; Siegle, Greg; Clark, Duncan
Abstract: Introduction: Growing evidence links later circadian timing during adolescence to worse sleep, more severe depression, and greater alcohol involvement, perhaps due to circadian misalignment and sleep restriction imposed by early school start times. School schedules initially shifted later during the COVID-19 pandemic, which hypothetically should reduce circadian misalignment and sleep restriction for adolescents with later circadian timing, and thus may mitigate any problems with sleep, depression, and alcohol. Here we used the pandemic as a natural experiment to test whether adolescent drinkers with later circadian timing, relative to those with earlier circadian timing, showed improved sleep, depressive symptoms, and alcohol involvement. Methods: We studied 42 high school students reporting alcohol use (aged 16-18; 27 female participants), assessing circadian phase via the dim light melatonin onset (DLMO) during pre-pandemic conditions, and then following them over four remote assessments every 3 months during the pandemic. Sleep characteristics were assessed via the Munich Chronotype Questionnaire, depressive symptoms were assessed via the Quick Inventory of Depressive Symptomatology, and alcohol use was assessed via a 90-day Timeline Followback. Mixed-effect models focused on the pre-pandemic baseline, COVID baseline (Apr/May 2020), and COVID-9-mo (Jan/Feb 2021) timepoints, and covaried for age, time between pre-pandemic and COVID baselines, and current school/work status. Results: In the pre-pandemic period, compared to those with earlier circadian timing, individuals with later circadian timing (later DLMO) got relatively less sleep (shorter total sleep time) on school nights. During the pandemic, earlier and later groups no longer differed on school night sleep. Over the course of the pandemic, compared to the earlier group, individuals with later circadian timing also reported larger increases in alcohol use (number of drinks, drinking days, and maximum drinks). Individuals with later circadian timing reported relatively greater depressive symptoms both pre-pandemic and 9-months into the pandemic. Conclusion: While individuals with later circadian timing benefitted in terms of more school night sleep during the pandemic, this did not translate to mitigating depression or alcohol use. These findings suggest that later circadian timing may contribute to risk for depression and alcohol use over and above effects due to insufficient sleep. Support (If Any): Supported by grants from NIH (R01AA025626; P50DA046346).